Maternal Exposure to Alcohol and Low Birthweight: A Systematic Review and Meta-Analysis - Priscilla Perez da Silva Pereira; Fabiana Araújo Figueiredo Da Mata; Ana Claudia Morais Godoy Figueiredo; Roberta Borges Silva; Maurício Gomes Pereira
Abstract Objective To investigate the relationship between maternal exposure to alcohol and low birthweight (LBW). Methods The literature search was performed in January 2017 using the following electronic databases: Medline, Embase, LILACS, SciELO, Web of Science, Scopus, CINHAL, Proquest, and PsychInfo. The search strategy used the following terms: alcohol drinking, binge drinking, alcohol-related disorders, alcoholism, alcohol addiction/ use/abuse/consumption, light/moderate/social/low drinking, low birthweight, case-control studies, retrospective studies, and cohort studies. No restrictions regarding language or publication date were considered. The literature search yielded 2,383 articles, and after screening and eligibility assessment, 39 articles were included in the systematic review, and 38 studies were included in the meta-analysis. Results Maternal alcohol consumption was associated with LBWamong retrospective cohort studies (relative risk [RR] = 1.37; 95%CI [confidence interval]:1.10-1.77; I2 = 98.4%; p < 0.01). Prospective cohort studies (RR = 1.11; 95%CI: 0.98-1.25; I2 = 81.5%; p < 0.01), and case-control studies (odds ration [OR] = 1.16; 95%CI: 0.68-1.97; I2 = 61.2%; p = 0.05) showed no association between alcohol and LBW.No publication bias was identified, and the meta-regression showed that the sample size influenced the high heterogeneity among retrospective cohort studies. The subgroup analysis showed differences in association between groups when compared by sample size, type of adjustment, or crude measures and publication year. Conclusions We have not found an association between alcohol consumption during gestation and LBW in the analysis in all of the subgroups. In addition, we have found a high heterogeneity between the primary studies, which is related to methodological differences in the conduction of these studies.